2022
DOI: 10.21010/ajid.v16i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Mortality

Abstract: Background : Antibiotic resistance has been a long - debated topic since decades ago. The development of stronger, newer antibiotics, implementation of antibiotic stewardship and revised guidelines remain t he main focus of our society to prevent resistancy. But is it really resistancy that cause higher mortality to patients with multidrug resistance (MDR) infections? Methods : We conducted a cohort retrospective study from 2016 to 2019 in our Intensive care u nit (ICU). Antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
0
0
Order By: Relevance
“…Generally, the higher the score, the greater the risk of poor prognosis. 29 In patients with MDRB infections, Casadeval et al 30 discovered a significant relationship between mortality and APACHE score greater than 20, and Huiping Huang et al 31 also mentioned high APACHE II score as a risk factor for infections with drug-resistant bacteria, which is also consistent with the findings of our study. As the factors were accessible and objective, the infection and dead risk could be evaluated more fleetly and reliably using a nomogram tool than traditional methods.…”
supporting
confidence: 89%
“…Generally, the higher the score, the greater the risk of poor prognosis. 29 In patients with MDRB infections, Casadeval et al 30 discovered a significant relationship between mortality and APACHE score greater than 20, and Huiping Huang et al 31 also mentioned high APACHE II score as a risk factor for infections with drug-resistant bacteria, which is also consistent with the findings of our study. As the factors were accessible and objective, the infection and dead risk could be evaluated more fleetly and reliably using a nomogram tool than traditional methods.…”
supporting
confidence: 89%
“…In our study, the factors associated with death of patients with positive AR before, during, and after the pandemic were age, nationality, COVID-19 infection, smoking, liver disease, type of bacteria, and number of associated bacteria. Some of these factors, such as, COVID-19, smoking, and number of associated bacteria, were not reported previously; however, previous studies have reported old age, chronic liver disease, and bacterial infection (E. coli, K. pneumonia, A. baumanii) as factors associated with death of patients with positive AR [37][38][39][40]. In contrast, chronic renal diseases, ICU admission, inability to perform self-care, chronic lung diseases, occupation, septic shock, hypertension, improper use of empirical antibiotics, and body mass index were risk factors reported in some studies [37,39,[41][42][43].…”
Section: Discussionmentioning
confidence: 86%
“…Addressing the complex interplay between the lack of clean water and AMR demands a comprehensive approach rather than relying solely on reducing human antimicrobial usage. The solution should encompass improving access to safe water, implementing effective water treatment processes, improving antibiotic stewardship and public health literacy, reducing antibiotic use in agriculture and animal husbandry, and promoting the development of new antibiotics and alternative therapies [1,14,15,[26][27][28][29]. Several inventive techniques like solar photocatalysis and nanoparticle drug development have shown potential in addressing the lack of access to clean water and AMR [29,30].…”
Section: Introductionmentioning
confidence: 99%